Clinical and radiological factors predicting recurrence of chronic subdural hematoma: A retrospective cohort study. Issue 10 (October 2019) - Shen, Jun; Yuan, Lili; Ge, Ruixiang; Wang, Qifu; Zhou, Wei; Jiang, Xiao Chun; Shao, Xuefei
Highlights: Age >80 years, antiplatelet or anticoagulant use, GOS = 3, the volume of drainage ≥100 ml were significant related to the CSDH recurrence. Midline shift ≥10 mm, severe brain atrophy, and severe postoperative pneumocephalus were significant related to the CSDH recurrence. Midline shift, brain atrophy, postoperative pneumocephalus, and volume of drainage were independent risk factors for the CSDH recurrence. We first demonstrated that excessive drainage increased the risk of CSDH recurrence. The independent risk factors of the CSDH recurrence in previous studies and the present results were summarized as a comparison. Abstract: Background: Chronic subdural hematoma (CSDH) is commonly encountered in the elderly patients and the recurrence rate is still high, therefore, identifying risk factors for CSDH recurrence is essential. The present study aimed to identify clinical and radiological factors predicting the recurrence of CSDH. Methods: We retrospectively identified 461 patients with CSDH who underwent surgical evacuation in our department. Univariable analyses were performed at first, variables with a P -value of <0.05 were entered into multivariable logistic regression model. Kendall's tau-b test was used to evaluate the relationship between brain atrophy and postoperative pneumocephalus. Results: Univariable analyses revealed that patients with the following characteristics have a higher recurrence rate, including age ≥80 years, antiplatelet and/or anticoagulant use, GOS = 3, the volume of drainage ≥100 ml, midline shift ≥10 mm, severe brain atrophy, severe postoperative pneumocephalus. Multivariable logistic regression demonstrated that midline shift ≥10 mm, severe brain atrophy, severe postoperative pneumocephalus, and volume of drainage ≥100 ml were independent risk factors for CSDH recurrence. Kendall's tau-b test revealed that there was no correlation between brain atrophy and postoperative pneumocephalus. Conclusions: Midline shift ≥10 mm, severe brain atrophy, severe postoperative pneumocephalus, and volume of drainage ≥100 ml were independent risk factors for CSDH recurrence, CSDH patients with these characteristics should be taken precautions of recurrence and a closely follow-up should be carried out.